Green chemical processes developments in research and education - Benvenuto, Mark A. (Mark Anthony) (Green chemical processing ;, 2017)
The "greening" of industry processes - i.e., making them more sustainable - is a popular and often lucrative trend which has seen increased attention in recent years. Green Chemical Processes, the 2nd volume of Green Chemical Processing, covers the hot to.